Three-nucleon dynamics in dp breakup collisions using the WASA detector at COSY-Julich - Adlarson, P.; Augustyniak, W.; Bardan, W.; Bashkanov, M.; Bergmann, F. S.; Berlowski, M.; Bondar, A.; Buescher, M.; Calen, H.; Ciepal; Clement, H.; Czerwinski, E.; et al. (Physical Review C - Nuclear Physics, 2020)
The differential cross section for the H-1(d, pp)n breakup reaction at deuteron beam energy of 340 MeV has been measured with the use of the WASA detector at COSY-Jillich. The set of proton-proton coincidences registered at the Forward Detector has been analyzed on a dense grid of kinematic variables, giving in total around 5600 data points. The cross-section data are compared to theoretical predictions based on the state-ofthe-art nucleon-nucleon potentials, combined with a three-nucleon force or the Coulomb interaction or carried out in a relativistic regime.
CRIS-Team WoS Importer:2020-04-24